'A Stammering Bundle of Welsh Idealism': Arthur Trystan Edwards and Principles of Civic Design in Interwar Britain. (21st September 2018) - Shasore, N.E.
Abstract: This article provides the first account of key texts and concepts in the theory and criticism of Arthur Trystan Edwards. Edwards's notion of 'civic design', which emanated from the Liverpool School of Architecture in the second decade of the twentieth century, was part of a broader international trend (particularly in the US and Europe) towards formal, axial and monumental planning. Edwards imbued civic design with a philosophical and political sophistication that set him apart from many of his non-Modernist contemporaries. The article discusses the underlying precepts — such as 'subject', 'form', 'urbanity' and 'manners' — in some of Edwards's critical texts, including Good and Bad Manners in Architecture (1924). The final section traces his pioneering interest in high-density, low-rise housing, which culminated with the establishment of the Hundred New Towns Association in 1933–34.